Pendidikan Kesehatan terhadap Tingkat Pengetahuan dan Sikap Ibu Hamil tentang Upaya Pencegahan Stunting - Bulan Rexy Pratiwi; Abi Muhlisin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of health education on the level of knowledge and attitudes of pregnant women about stunting prevention. This study used the Pre-Experimental method with one group pre-test and post-test design. Based on the paired sample t-test assisted by SPSS 25.0 software on the effect of health education on the level of knowledge of pregnant women, a significance value was obtained (p-value 0.000 < 0.05) and the impact of health education on attitudes of pregnant women, the significance value is p-value 0.000 < 0.05. In conclusion, there is an influence of health education on the level of knowledge and attitudes of pregnant women. Keywords: Health Education, Attitude, Stunting, Level of Knowledge